The Effect Of Kenaf Loading And Hybridization Of Kenaf With Empty Fruit Bunch Fibers Or Halloysite Nanotube On Properties Of Natural Rubber Latex Foam - Kudori, Siti Nurul Izzati (2020)
Natural rubber latex foam (NRLF) become great interest to the society due to its function in various applications. However, the usage of natural filler in NRLF from previous literature are do not perform very well. The aim of this research was to produce NRLF with different component of kenaf and hybridization of kenaf with Empty Fruit bunch (EFB) and Halloysite Nanotube (HNT) in order to provide good mechanical and physical properties. The incorporation of kenaf in natural rubber latex foam (NRLF) was prepared by using Dunlop method. Morphology, tensile properties, density, compression, hardness and thermal aging of kenaf filled NRLF were analysed in this work. The different loading of kenaf core or bast (0,1,3,5,7 phr) was studied. The tensile strength, elongation at break (Eb) and compressive strength of kenaf core or bast filled NRLF samples decreased as the loading of kenaf was increased. However, the modulus at 100% elongation (M100), hardness and density of NRLF increased with increasing kenaf loadings. The addition of kenaf core into NRLF increased the swelling percentage and retention percentage of aging compared to the kenaf bast. Scanning electron microscope (SEM) results indicated that the fibrous kenaf bast had strong adhesion compared to the particulate kenaf core, resulting higher tensile strength, Eb and compression strength. The effect of different size of kenaf bast (97, 144, 200 μm) filled NRLF was also studied. It revealed that the smaller size of kenaf filled NRLF showed higher in tensile properties, compression strength, compression set and hardness at the same kenaf loading. The size of the window cell increases as size of the filler increased. The hybridization of kenaf/ EFB showed that the size of cell window become larger with increasing EFB loading resulting in reduction of mechanical properties. For thermal aging, EFB filled NRLF has higher retention percentage of tensile strength and M100 compared to kenaf filled NRLF. The substitution of halloysite nanotube in kenaf filled NRLF promotes the cell window to coalesce each other and increase the formation of larger cell window.